A comparative study between the chinese writer Lu Xun and Naguib Mahfouz - Khataybeh, Yousef Saleh Ibrihim (Journal of Arabic Language Sciences and Literature, 2022)
The Chinese writer (Lu Xun) and Naguib Mahfouz are considered the two deans of modern Chinese and Arabic literature, and both of them have achieved impressive results in their fields. Four chapters and a conclusion. In the introduction, I talked about each of the writers and what they achieved in their field. In the first chapter, I talked about the viewpoint of each of the writers towards the West, and I compared their views on this subject. In the second chapter, I dealt with how each of them viewed women, and compared their two views towards women. In the third chapter, I dealt with how each of them dealt with the concept of the intellectual and how he looked at it, comparing their opinions.
Keywords: Chinese literature; Lu Xun; Naguib Mahfouz